LANGUAGE AND VISUAL STYLE IN POLITICAL DISCOURSE: REFLECTIONS ON IDENTITY AND ITS IMPACT ON THE PUBLIC - Erwin, Erwin; Maryani, Sri (JURNAL KONFIKS, 2025)
This study explores how language choices and visual styles in political communication serve to reflect candidates’ identities, express ideological narratives, and shape public perception. Utilizing a qualitative approach with ethnographic methods, the research involves participatory observation, in-depth interviews with campaign teams, and analysis of visual campaign materials from local political contexts. Grounded in sociopragmatic stylistics theory, the study examines how verbal and visual elements interact within specific socio-cultural frameworks to construct persuasive political messages. Findings show that the strategic use of local languages and culturally embedded symbols enhances emotional engagement between candidates and constituents. Language that aligns with regional identity fosters trust and relatability, reinforcing the authenticity of the candidate’s image. Visual aspects such as color selection, layout design, typography, and symbolic imagery play a crucial role in reinforcing ideological positioning and constructing coherent public personas. These visual cues often communicate values, aspirations, and affiliations more powerfully than verbal language alone. However, the research also uncovers the potential for dissonance when verbal messages are not visually supported or when visuals contradict spoken rhetoric. Such inconsistencies can weaken the intended message and lead to misinterpretation or distrust among the public. The study’s novelty lies in its integration of ethnographic methodology with sociopragmatic stylistics to examine local-level political campaign communication an area still underexplored in Indonesian political studies. These insights provide valuable implications for academics, political strategists, and communication practitioners in designing more coherent, context-sensitive, and impactful political campaigns that resonate with target audiences.